Comparison of the effectiveness of repeated injections of onabotulinum toxin A for refractory idiopathic detrusor overactivity: analysis of an open label extension of a randomized trial (the RELAX study). Issue 4 (26th August 2016) - Owen, Rhiannon K.; Abrams, Keith R.; Mayne, Christopher; Slack, Mark; Tincello, Douglas G.
Abstract : AIMS: To assess effects of repeat treatment with onabotulinumtoxin A (onaBoNT‐A) in women with refractory idiopathic detrusor overactivity (DO). METHODS: Analysis of an open‐label extension study of a large randomized placebo controlled trial of onaBoNT‐A. Participants had been randomized to receive 200 IU onaBoNTA or placebo and were offered up to two further onaBoNTA injections over a 5‐year period. For this analysis, the primary outcome was duration of treatment effect by patient‐reported symptom return. Weibull proportional hazards regression models were fitted in a Bayesian framework to estimate missing times. Multivariable hazard regression analysis (hazard ratio, 95% credible intervals (HR, 95% CrI) compared repeated injections adjusting for differences in baseline symptom severity. Secondary outcomes included inter‐injection interval, incontinence, urgency, and voiding episodes 6 weeks after injection. RESULTS: Four hundred and forty‐two active injections were administered: 228 patients had one, 155 had two, and 59 had three injections. Time to symptom return for injection number 1 and 2 was 84 (95%CI: 63, 112) and 180 (95%CI: 135, 223) days, respectively. Median inter‐injection intervals for receiving second and third injection were 266 days (range: 130, 1400) and 372 days (range: 134, 1283). No statistically significant differences in symptom outcomes or time to symptom return (HR 0.88, 95% CrI 0.37, 2.07 for injection 2, HR 0.33, 95% CrI 0.09, 1.03 for injection 3) were observed. CONCLUSIONS: Repeated onaBoNT‐A injections have consistent efficacy and duration of action. There appears to be long‐term placebo effects in both groups of randomized patients, with implications for open‐label extension studies.